Imunitní trombocytopenie jako komplikace akutních infekčních onemocnění -- kazuistiky - Smíšková, Dita; Blechová, Zuzana; Polanecká, Libuše; Zítová, Jitka; Podojilová, Marie; Smíšek, Petr (Klinicka mikrobiologie a infekcni lekarstvi, 2013)
Immune thrombocytopenia (immune thrombocytopenic purpura, ITP) is an acquired autoimmune disease, mediated by antibodies against platelet glycoproteins. ITP can develop in the context of other disorders (secondary ITP), including acute and chronic infections (HIV, H. pylori, HCV, HBV, CMV, EBV, VZV, parvovirus B19, rubella, etc.). The case reports present two children and one adult with ITP complicating VZV, EBV and HAV infections. Corticosteroids are usually initial drugs, but they are controversial in case of ITP during acute infections. Intravenous immunoglobulins are preferred, especially in children, because of their smaller suppression of inflammatory response. Two of the patients were successfully treated with intravenous immunoglobulins. In the remaining patient, corticosteroid therapy had good but delayed effects as compared to immunoglobulins.
Keywords: hepatitida A; předškolní dítě; infekce virem Epsteina-Barrové; Humans; lidé; Acute Disease; Female; Male; akutní nemoc; Adult; Purpura, Thrombocytopenic, Idiopathic; mužské pohlaví; Hepatitis A; Chickenpox; ženské pohlaví; Child, Preschool; idiopatická trombocytopenická purpura; dospělí; plané neštovice; Epstein-Barr Virus Infections